Magnetic, spectroscopic and biological properties of copper(II) complexes of the tridentate ligand, α-N-methyl-S-methyl-β-N-(2-pyridyl)methylenedithiocarbazate(NNS) and the X-ray crystal structure of the [Cu(NNS)I2] complex - Akbar Ali, Mohammad; Huq Mirza, Aminul; Haji Iran, Malai Shah; Butcher, Ray J.; Tarafder, M.T.H.; Boon Keat, Tan; Manaf Ali, A. (Springer, 2002)
Copper(II) complexes of general formula, Cu(NNS)X2 · nH2O (NNS = the 2-formylpyridine Schiff base of N-methyl-S-methyldithiocarbazate; X = Cl-, Br-, I-, NCS-; n = 0, 2) have been synthesized and characterized by elemental analysis and by magnetic and spectroscopic techniques. Based on magnetic and spectroscopic data, a monomeric five-coordinate square-pyramidal structure is assigned to these complexes. The crystal and molecular structure of [Cu(NNS)I2] has been determined by X-ray diffraction. The complex has a monomeric square-pyramidal structure with the ligand coordinated to the copper(II) ion via the pyridine nitrogen atom, the azomethine nitrogen atom and the thione sulfur atom. The fourth and fifth coordination sites are occupied by the iodide ligands. Antimicrobial tests indicate that Schiff base is inactive against the bacteria, Bacillus subtilis (mutant defective DNA repair), Pseudomonas aeruginosa, methicillin resistant Staphylococcus aureus and Bacillus subtilis (wild type) and weakly active against the fungi, Candida albicans, Candida lypolytica, Saccharomyces cereviseae and Aspergillus ochraceous but its copper(II) complexes, Cu(NNS)X2 are strongly active against these organisms. A cytotoxicity study of the compounds against leukemic and cervical cancer cells showed that the Schiff base is inactive, but the complexes, [Cu(NNS)I2] and [Cu(NNS)(NCS)2] · 2H2O exhibit significant activity against cervical cancer cells with CD50 values of 4.8 and 4.2 μg, respectively.